Phase control during the synthesis of nickel sulfide nanoparticles from dithiocarbamate precursors. Issue 21 (13th May 2016) - Roffey, Anna; Hollingsworth, Nathan; Islam, Husn-Ubayda; Mercy, Maxime; Sankar, Gopinathan; Catlow, C. Richard A.; Hogarth, Graeme; de Leeuw, Nora H.
Abstract : Square-planar nickel bis(dithiocarbamate) complexes, [Ni(S2 CNR2 )2 ], have been prepared and utilised as single source precursors for a range of nanoparticulate nickel sulfide phases. Through changing concentration, temperature and the use of a thiuram disulfide additive. Abstract : Square-planar nickel bis(dithiocarbamate) complexes, [Ni(S2 CNR2 )2 ], have been prepared and utilised as single source precursors to nanoparticulate nickel sulfides. While they are stable in the solid-state to around 300 °C, heating in oleylamine at 230 °C, 5 mM solutions afford pure α-NiS, where the outcome is independent of the substituents. DFT calculations show an electronic effect rather than steric hindrance influences the resulting particle size. Decomposition of the iso-butyl derivative, [Ni(S2 CN i Bu2 )2 ], has been studied in detail. There is a temperature-dependence of the phase of the nickel sulfide formed. At low temperatures (150 °C), pure α-NiS is formed. Upon raising the temperature, increasing amounts of β-NiS are produced and at 280 °C this is formed in pure form. A range of concentrations (from 5–50 mM) was also investigated at 180 °C and while in all cases pure α-NiS was formed, particle sizes varied significantly. Thus at low concentrations average particle sizes were ca. 100 nm, but at higher concentrations they increased to ca. 150 nm. The addition of two equivalents of tetra-iso-butyl thiuram disulfide, ( i Bu2 NCS2 )2, to the decomposition mixture was found to influence the material formed. At 230 °C and above, α-NiS was generated, in contrast to the results found without added thiuram disulfide, suggesting that addition of ( i Bu2 NCS2 )2 stabilises the metastable α-NiS phase. At low temperatures (150–180 °C) and concentrations (5 mM), mixtures of α-NiS and Ni3 S4, result. A growing proportion of Ni3 S4 is noted upon increasing precursor concentration to 10 mM. At 20 mM a metastable phase of nickel sulfide, NiS2 is formed and as the concentration is increased, α-NiS appears alongside NiS2 . Reasons for these variations are discussed.